Effect of gender on fatigue and recovery following maximal intensity repeated sprint performance - Laurent, C. M.; Green, J. M.; Bishop, P. A.; Sjökvist, J.; Schumacker, R. E.; Richardson, M. T.; Curtner-Smith, M. (The Journal of Sports Medicine and Physical Fitness, 2010)
Aim. This study investigated the effects of gender on repeated, maximal-intensity intermittent sprint exercise following variable day-to-day recovery periods. Methods. Sixteen volunteers (8 men, 8 women) performed four trials of high-intensity intermittent sprint exercise consisting of three bouts of eight 30 m sprints (total of 24 sprints). Following completion of the baseline trial, in repeated-measures design, participants were assigned, in counter-balanced order, variable recovery periods of 24, 48, and 72 h whereupon they repeated an identical exercise trial. Results. Results from a series of 4 (trial) x 3 (bout) repeated measures ANOVAs revealed men produced significantly (P < 0.01) faster times throughout all bouts and trials of repeated sprint exercise. Additionally, women exhibited significantly lower (P < 0.05) blood lactate concentration and significantly lower (P < 0.05) decrement in performance, indicating increased resistance to fatigue during repeated exercise sessions. There were no significant differences (P > 0.05) between genders for heart rate or rating of perceived exertion during or following trials. There were no significant differences for overall sprint performance within either gender among trials. Conclusions. These results indicate men, while able to produce higher absolute power outputs (i.e., lower sprint time), demonstrate higher decrement scores within a trial compared to women, thus suggesting women may recover faster and fatigue less. Also, gender differences affecting recovery within in a trial were observed to be diminished between trials (i.e., day-to-day recovery) of maximal intermittent sprint work evidenced by the observed stability of performance between trials following various recovery durations.